SISTEM TANAM JAJAR LEGOWO PADA PERTUMBUHAN JAGUNG MANIS (Zea mays L. Saccharata) - Erungan Feidy; Rotinsulu Wiske Ch; Wanget Sesilia A; Demmasabu Langimanapa S (Universitas Sam Ratulangi, 2020)
ABSTRACTThe legowo row planting system on sweet corn growth aims to determine which legoworow cropping system is appropriate for sweet corn plants and is able to have an influence onthe growth of sweet corn plants. Implemented at the UNSRAT Experimental Garden inTomohon, using a randomized block design method. This research was conducted with threetreatments, namely: legowo row 2: 1, legowo row 3: 1, and conventional. With the spacing forlegowo row 50 x 25 cm and conventional 70 x 25 cm. Observation variables include plantheight and number of leaves which data are taken each week. The results of this study were theuse of legowo row 2: 1 and legowo row 3: 1 planting systems with a spacing of 50 cm x 25 cmand a conventional planting system with a spacing of 70 cm x 25 cm on sweet corn in Tomohonhad no effect on vegetative growth.Keywords: legowo row, sweet corn, vegetative growth.